Detecting sleep and physical activity changes across the perinatal period using wearable technology - Elizabeth A. Claydon; Christa L. Lilly; Erin D. Caswell; Dawna C. Quinn; Shon P. Rowan (BMC, 2024)
Abstract Background Pregnant women may not experience disruptions in sleep duration throughout the course of pregnancy, however, their sleep quality is dramatically impaired. Sleep quality deteriorates throughout pregnancy, reaching its lowest in the third trimester. The purpose of this study was to understand the change in sleep patterns across the perinatal period, as well as the impact of physical activity on sleep. Methods A total of 18 physically active women trying to conceive wore a WHOOP strap (a fitness monitor) across the perinatal period. Daily behavior changes were tracked including time awake, hours in deep sleep, physical activity, and time in moderate to vigorous physical activity. Results Women maintained overall physical activity levels during and after pregnancy and averaged 20.70 min of physical activity and 6.97 h of sleep per day. Total time in awake hours increased postpartum. Moderate-vigorous physical activity minutes improved deep sleep hours overall (Est. = 0.003 h, p < 0.0001) and during pregnancy (Est. = 0.00001 h, p = 0.0004). Similar effects were found for all activity minutes, although in post pregnancy the moderating impact of activity minutes no longer maintained significance (p = 0.09).\. Conclusions Wearable technology, including fitness monitors such as WHOOP straps offer a convenient and less invasive way to track sleep and physical activity during the perinatal period. The findings of this study indicate a positive connection between sleep and engaging in moderate to vigorous activity and any activity throughout the perinatal period. These results may help inform clinical and practical recommendations for physical activity to improve sleep outcomes for pregnant women.